Scientific Reasoning and Argumentation: Advancing an Interdisciplinary Research Agenda in Education - Frank Fischer; Ingo Kollar; Stefan Ufer; Beate Sodian; Heinrich Hussmann; Reinhard Pekrun; Birgit Neuhaus; Birgit Dorner; Sabine Pankofer; Martin Fischer; Jan-Willem Strijbos; Moritz Heene; et al. (EARLI, 2014)
Scientific reasoning and scientific argumentation are highly valued outcomes of K-12 and higher education. In this article, we first review main topics and key findings of three different strands of research, namely research on the development of scientific reasoning, research on scientific argumentation, and research on approaches to support scientific reasoning and argumentation. Building on these findings, we outline current research deficits and address five aspects that exemplify where and how research on scientific reasoning and ar-gumentation needs to be expanded. In particular, we suggest to ground future research in a conceptual frame-work with three epistemic modes (advancing theory building about natural and social phenomena, artefact-centred scientific reasoning, and science-based reasoning in practice) and eight epistemic activities (problem identification, questioning, hypothesis generation, construction and redesign of artefacts, evidence generation, evidence evaluation, drawing conclusions as well as communicating and scrutinizing scientific reasoning and its results). We further propose addressing the domain specificities and domain generalities of scientific reasoning and approaches to its facilitation as well as investigating the role of epistemic emotions in scientific reasoning, the social context of SRA, and the influence of digital technologies on scientific reasoning and argumentation.